Determinant Factors of Leverage – Based Firm Value, with Management Ownership Role as a Moderation - Aprih Santoso; Muslim; Ardiani Ika Sulistyawati; Dede Hertina; Alfiana (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to analyze leverage on firm value and the moderating role of management ownership variables in the influence of leverage on the value of manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2020. The population of this research is all manufacturing companies on the Indonesia Stock Exchange for the 2015-2020 period. . The sampling technique in this study uses purposive sampling with the criteria of manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2020 period, with the total number of shares owned by the company's management above 1% of all outstanding shares so that the sample is 162. To see the type of moderation then used two equation models, so that the regression model equation. The data was processed with SPSS'26 software. The result of the research is that leverage has a positive and significant effect on firm value. Management ownership is proven to moderate the effect of leverage on firm value. The existence of management ownership in its interaction with leverage and firm value is a pure moderator